2018
DOI: 10.51985/jbumdc2018094
|View full text |Cite
|
Sign up to set email alerts
|

Frequency And Shape Of Torus Palatinus In Relation To Age And Gender In Karachi

Abstract: Objective: The aim of this study was to determine the frequency and shape of torus palatinus and to assess its gender and age-related differences in the population of Karachi, the metropolitan city of Pakistan. Methodology: This was a cross sectional study with non-probability convenience sampling method conducted at Bahria University Medical & Dental College (BUMDC), Karachi. The presence of tori was observed by clinical examination and palpation. The shape was also investigated by presence or absence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…On the contrary, in Karachi, Pakistan, Mirza et al found that TP was more prevalent (53.9%) in males (31).…”
Section: Age and Sexmentioning
confidence: 92%
“…On the contrary, in Karachi, Pakistan, Mirza et al found that TP was more prevalent (53.9%) in males (31).…”
Section: Age and Sexmentioning
confidence: 92%